2013
DOI: 10.1021/jz4022415
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability and Activity for Water Oxidation in Alkaline Media with Bismuth Vanadate Photoelectrodes Modified with a Cobalt Oxide Catalytic Layer Produced by Atomic Layer Deposition

Abstract: Atomic-layer deposition (ALD) of thin layers of cobalt oxide on n-type BiVO4 produced photoanodes capable of water oxidation with essentially 100% faradaic efficiency in alkaline, pH = 13 electrolytes. By contrast, under the same operating conditions, BiVO4 photoanodes without the Co oxide catalytic layer exhibited lower faradaic yields, of ca. 70%, for O2 evolution and were unstable, becoming rapidly photopassivated. High numbers (>25) of ALD cycles of Co oxide deposition gave electrodes that displayed poor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 27 publications
2
93
0
Order By: Relevance
“…[25] By taking this into account, the 4.22 mA cm À2 photocurrent density that we observe with the combination of BiVO 4 and micromorph Si corresponds to an apparent h STH of 5.2 %, which represents the current benchmark for standalone water-splitting devices based on a metal oxide photoelectrode. [9][10]26] Although the increase in h STH (4.9 [9] to 5.2 %) may seem incremental, the implication is very significant. Recent technoeconomic analyses have shown that efficiency is the most important knob in determining the resulting cost of hydrogen.…”
Section: à2mentioning
confidence: 98%
See 2 more Smart Citations
“…[25] By taking this into account, the 4.22 mA cm À2 photocurrent density that we observe with the combination of BiVO 4 and micromorph Si corresponds to an apparent h STH of 5.2 %, which represents the current benchmark for standalone water-splitting devices based on a metal oxide photoelectrode. [9][10]26] Although the increase in h STH (4.9 [9] to 5.2 %) may seem incremental, the implication is very significant. Recent technoeconomic analyses have shown that efficiency is the most important knob in determining the resulting cost of hydrogen.…”
Section: à2mentioning
confidence: 98%
“…With a theoretical photocurrent density of 7.5 mA cm À2 for BiVO 4 , there is plenty of room for improvement by the combination of BiVO 4 and single-junction a-Si:H. In contrast, only little improvements are possible for the BiVO 4 /double-junction Si cell devices, in which the total photocurrent density is already close to the maximum photocurrent density of the double-junction Si cell. [9,10,17] A configuration with a single-junction a-Si:H cell therefore seems the most promising route for the further development of hybrid PEC/PV devices.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the overpotentials associated with the anode and cathode reactions and other system losses, the thermodynamic potential needed to split water, 1.23 V under standard conditions, imposes constraints on the operating photovoltage produced by the light absorber. Intensive efforts have focused on transition-metal oxides (TMOs) for watersplitting applications [4][5][6]. An alternative approach involves dual light absorbers, analogous to the Z-scheme of natural photosynthesis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…4a was predominantly associated with the faradaic oxidation of H 2 O to O 2. Direct verication of this hypothesis was obtained using an oxygen detector, 20 which revealed that n-CdTe/TiO 2 /Ni samples Oxygen production detected by a fluorescent probe and derived from coulometry during constant potential electrolysis at 1.23 V vs. RHE in pH ¼ 14 KOH(aq). In (a), the n-CdTe/TiO 2 /Ni electrode was illuminated by a Xenon arc lamp that had been calibrated to provide 100 mW cm À2 of simulated AM1.5G illumination; in (b), 20 mW cm À2 was used to prevent bubble formation.…”
mentioning
confidence: 99%